"Down-to-Earth TV dramas": The reception of authenticity, reality, and modality in Danish TV dramas. (December 2021) - Kaptan, Yeşim
This article investigates how Turkish audiences conceptualize authenticity in their engagement with foreign television (TV) productions in the case of Danish TV dramas. The theoretical notion of authenticity is juxtaposed with empirical material from fieldwork interactions, focus group interviews, and one-on-one interviews conducted with Turkish audiences between 2016 and 2018. By employing a semiotic analysis of fieldwork data, I argue that Turkish audiences attribute authenticity to the Danish TV drama series according to a socially created modality (truth value of a sign). This article draws on accounts about modality markers in TV drama series such as authentic portrayals of Danish TV characters and plausible-realistic depictions as a verisimilitudinous representation of everyday life. In the context of cross-cultural television viewing practices, the way Turkish audiences attribute meaning to Danish TV series in terms of authenticity, realism, and modality reveals a distinct differentiation between Danish TV dramas and other nationally and globally circulating media products.